2018
DOI: 10.1088/1755-1315/139/1/012032
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in managing freshwater fishery resource through Lebak Lebung Auction approach: a case study in Pangkalan Lampam District Ogan Komering Ilir Regency

Abstract: Abstract. Responsible management of fishery resources has been a tradition of Ogan Komering Ilir (OKI) of South Sumatera for generations. It was recorded that since 1630 the Dutch Government had made auction policy for managing water territory in OKI Regency as an effort to preserve nature and to avoid the conflict of inland water ownership. Currently, the communitybased management model has been adopted by local governments into formal regulations, known as Regional Regulation on Auction of Flood Water Swamp … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…After auctioning (2), the winner, known as Pengemin, must complete the payment (4), which can be used for fisheries activities for one year, and fishermen could rent an auction area from Pengemin. However, when the payment is not completed, Pengemin will be charged 10% or threats retained for three (Muslimin and Suadi, 2018). (Muslimin and Suadi, 2018) This study used an overview of the stages of L3S implementation in general from Muslimin and Suadi's (2018) research (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After auctioning (2), the winner, known as Pengemin, must complete the payment (4), which can be used for fisheries activities for one year, and fishermen could rent an auction area from Pengemin. However, when the payment is not completed, Pengemin will be charged 10% or threats retained for three (Muslimin and Suadi, 2018). (Muslimin and Suadi, 2018) This study used an overview of the stages of L3S implementation in general from Muslimin and Suadi's (2018) research (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…The accumulated results were distributed equally in OKI, with adjusted percentages for villages without objects. However, research results found different facts, and the discourse on opening access was precisely a cover for access for local communities (Muslimin and Suadi, 2018;Grantham, 2015).…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…The history of using flooded swamp public waters, especially what is often called lebak and lebung along with rivers in OKI District, has been traced from various sources [7,8,19,20]. The initial development of the L3 practice took its point until the Palembang Sultanate was continued by the Dutch East Indies colonial government, which pulled the wheels of government.…”
Section: Development Of L3s Institutionsmentioning
confidence: 99%
“…This research was conducted in Sirah Pulau Padang, Jejawi, Pedamaran sub-district OKI Regency, South Sumatra. The location selection was carried out purposively with the consideration of implementing L3S, a strategic location close to the center of government, including sub-districts with as many as 19…”
mentioning
confidence: 99%